Analysis Validity and Readability of Local Potential-Based Textbooks on Plantae Materials to Improve Students’ Science Literacy - Nashikhah, Khoirun; Rusilowati, Ani (Unnes Science Education Journal, 2024)
Textbooks based on local potential of plantae material can be used to improve the science literacy of students at the junior high school. The aim of this study is to analysis validity and readability of textbooks based on local potential to improve student’s science literacy. Data analysis was carried out to obtain scores of validation results by material experts and media experts as well as the readability of textbooks by students in small-scale trials. The results of expert validation questionnaire showed an average score for the aspects of material feasibility and media feasibility were 93.36% and 89.29% with a very valid category. The readability test results showed that the textbook had an average score of 71% with understandable criteria. Based on the results of this study, it can be concluded that textbooks based on local potential of plantae material can be used in student learning. This research contributes to the availability of textbooks based on local potential of plantae material. The research has implications for educational practitioners to help improve students’ science literacy.